Capacidade antimicrobiana do ácido peracético e do álcool na desinfecção de pontas de seringas tríplices - Marchi, Karen de (2022)
The surfaces of dental equipment are contaminated during appointments. The triple syringe is an item considered critical for the control of infections, since it comes into contact with the saliva and blood of patients. This study aimed to compare the antimicrobial capacity of 0.2% and 0.5% peracetic acid products and 70% alcohol, in the disinfection of triple syringe tips, in order to contribute to a better control of cross-contamination in dental care. Samples of 30 triple syringes were collected before and after disinfection with the chosen products. After the first collection, the syringes were divided into three groups: G1 (AP0.2): disinfection with 0.2% peracetic acid; G2 (AP0.5): disinfection with 0.5% peracetic acid; and, G3 (A70): disinfection with 70% ethyl alcohol. The samples were sown in brain-heart agar, to verify the growth of bacteria, and in Sabourad agar, to verify the growth of fungi. After being incubated at 37°C for 48 hours, the growth of colony forming units (CFUs) were counted and compared in the two moments. There was bacterial growth (Gram-negative bacilli) in 100% of the samples, before and after the disinfection procedures. Fungal growth was small, all of which were eliminated after disinfection. The disinfectants tested in this study were not effective in eliminating Gram-negative bacillary bacteria, but they were effective in eliminating fungi present in the tips of triple syringes of dental equipment, showing no difference in effectiveness between the products tested.